The Role of Adoption in Facilitating the Social Reintegration of Child Survivors of Sexual Abuse - Ismawati, Sri; Harefa, Safaruddin; Herlina, Herlina; Hertini, Mega Fitri; Lolita, Lolita (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
Sexual violence against children, particularly when it occurs within the family environment, constitutes a structural issue with long-term consequences for a child's psychological well-being, social functioning, and identity formation. This study aims to examine the effectiveness of current social reintegration policies for child victims of sexual violence and to propose an alternative, adoption-based model that is holistic and centered on the best interests of the child. Utilizing a qualitative socio-legal and interpretive approach, data were collected through observations and in-depth interviews with child protection institutions in West Kalimantan and the city of Pontianak. The findings indicate that the existing protection system fails to comprehensively meet the needs of victims, as it remains fragmented, short-term in orientation, and lacks adequate psychosocial support. The household, ideally a space of safety, was found to be the most common setting for abuse, with perpetrators often coming from within the immediate family circle. The novelty of this research lies in its proposed adoption-based social reintegration model, which integrates legal frameworks, developmental psychology, and social solidarity into a single comprehensive protection system. This model highlights the importance of institutional support, inter-agency collaboration, and community engagement as strategic measures for victim recovery and for breaking the cycle of intergenerational violence. It is hoped that these findings will contribute both to the academic discourse and to the strengthening of child protection policies in Indonesia.